1998
DOI: 10.1097/00007632-199808150-00018
|View full text |Cite
|
Sign up to set email alerts
|

Acute Nontraumatic Spinal Epidural Hematomas

Abstract: The results of the current series demonstrate both the superiority of magnetic resonance imaging for diagnosis of SSEH as well as the necessity of early decompressive surgery in cases of sensorimotor paralysis after SSEH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(29 citation statements)
references
References 14 publications
0
27
0
2
Order By: Relevance
“…Only ten cases of pregnant women with SCEH have been described in the literature to date (Table 1). The SSEH is usually posterior or posterolateral to the thecal sac [912]. …”
Section: Discussionmentioning
confidence: 99%
“…Only ten cases of pregnant women with SCEH have been described in the literature to date (Table 1). The SSEH is usually posterior or posterolateral to the thecal sac [912]. …”
Section: Discussionmentioning
confidence: 99%
“…Significantly better neurologic recovery was associated with incomplete versus complete neurologic deficits and shorter duration of time between onset of neurologic symptoms and surgery (<12 h) [20]. Other groups have found that neurologic recovery depends largely on the time interval between the onset of symptoms and surgical decompression [21]. …”
Section: Discussionmentioning
confidence: 99%
“…SSEH represents a rare spinal emergency, with a frequency accounting for less than 1% of spinal epidural space- occupying lesions 2,3. Jackson first described SSEH in a 14-year-old female in 1869,5 and the first surgically-treated case was reported by Bain in 1897 6.…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…The presence of concomitant cranial nerve signs or facial weakness generally prompts a search for cerebral etiologies such as stroke, neoplasms or inflammatory processes, while it may occasionally be due to a lesion located in the high cervical spinal cord 1. In this concise review, we describe the features of spontaneous spinal epidural hematoma (SSEH), which is a rare cause of spinal cord compression and a neurological emergency requiring prompt diagnosis and management to prevent morbidity and mortality 2,3. Most SSEH patients present with either paraplegia or tetraplegia; however, there are numerous descriptions about acute hemiparesis as an initial manifestation of SSEH, which may lead physicians to include an acute ischemic cerebrovascular event as a diagnostic consideration,4 thus leading to the concept that SSEH should be included in the large list of stroke mimics.…”
Section: Introductionmentioning
confidence: 99%